Mechanism and therapeutic window of a genistein nanosuspension to protect against hematopoietic-acute radiation syndrome - Landauer, Michael R (J Radiat Res, 2019)
There are no FDA-approved drugs that can be administered prior to ionizing radiation exposure to prevent hematopoietic–acute radiation syndrome (H-ARS). A suspension of synthetic genistein nanoparticles was previously shown to be an effective radioprotectant against H-ARS when administered prior to exposure to a lethal dose of total body radiation. Here we aimed to determine the time to protection and the duration of protection when the genistein nanosuspension was administered by intramuscular injection, and we also investigated the drug’s mechanism of action. A single intramuscular injection of the genistein nanosuspension was an effective radioprotectant when given prophylactically 48 h to 12 h before irradiation, with maximum effectiveness occurring when administered 24 h before. No survival advantage was observed in animals administered only a single dose of drug after irradiation. The dose reduction factor of the genistein nanosuspension was determined by comparing the survival of treated and untreated animals following different doses of total body irradiation. As genistein is a selective estrogen receptor beta agonist, we also explored whether this was a central component of its radioprotective mechanism of action. Mice that received an intramuscular injection of an estrogen receptor antagonist (ICI 182,780) prior to administration of the genistein nanosuspension had significantly lower survival following total body irradiation compared with animals only receiving the nanosuspension (P < 0.01). These data define the time to and duration of radioprotection following a single intramuscular injection of the genistein nanosuspension and identify its likely mechanism of action.